Nematode Management in Residential Lawns - William T. Crow (EDIS, 2013)
Plant-parasitic nematodes are among the least understood and most difficult pests to manage on turfgrass in Florida. They are very small, and most can only be seen with the aid of a microscope. They use a stylet to puncture plant cells, to inject digestive juices into them, and to ingest plant fluids. The most reliable way to determine whether plant-parasitic nematodes are involved in a turf problem is to have a nematode assay conducted by a professional nematode diagnostic lab. This 6-page fact sheet was written by William T. Crow and published by the UF Department of Entomology and Nematology, April 2013.